1997
DOI: 10.1136/adc.77.4.342
|View full text |Cite
|
Sign up to set email alerts
|

An epidemic of acute postinfectious glomerulonephritis in Armenia

Abstract: Aim-To evaluate the presentation and course of acute postinfectious glomerulonephritis (APGN), which has increased dramatically in Armenia after serious deterioration in the living conditions. Study design-Observational study, based on case notes, of a large homogeneous group of patients hospitalised for APGN at one centre over a five year period (1992-6). Patients-474 patients aged <16 years with a diagnosis of APGN.Results-The annual number of patients increased tenfold from 19 (average 1992/3) to 196 in 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
41
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 18 publications
6
41
0
3
Order By: Relevance
“…12 Our study showed that most patients with AGN were older than 6 years with a boy to girl ratio of 1.4:1. Our subjects were of lower socioeconomic status than those in the study in Benin city.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…12 Our study showed that most patients with AGN were older than 6 years with a boy to girl ratio of 1.4:1. Our subjects were of lower socioeconomic status than those in the study in Benin city.…”
mentioning
confidence: 53%
“…Table 3 shows the similarities and differences of observations between our study and other investigators. 12,13,15,19,21 Patients with AGN have an expanded extracellular fluid volume secondary due to sodium and water retention leading to clinical manifestations of AGN and generalized circulatory congestion. Although circulatory congestion is similar to primary fluid overload, there is no evidence of abnormality in the heart and blood vessel.…”
mentioning
confidence: 99%
“…In Rajajee et al study 13 [12][13][14]5 In the present study, at the time of presentation 82.5% of patients had low levels of serum C3 suggesting post infectious glomerulonephritis. Normal C3 at the time of onset of disease was present in 17.5% of patients.…”
supporting
confidence: 45%
“…DPGN is known to be post-infectious in nature and in majority of cases it is seen following streptococcal infection. In fact in Armenia, tenfold rise was seen in DPGN in children, following sudden deterioration in socioeconomic conditions [9]. Although some decline has been reported in a South Indian hospital [4], two other Indian studies i.e.…”
Section: Discussionmentioning
confidence: 97%